2013
DOI: 10.1002/dneu.22076
|View full text |Cite
|
Sign up to set email alerts
|

Collapsin response mediator protein 4 affects the number of tyrosine hydroxylase‐immunoreactive neurons in the sexually dimorphic nucleus in female mice

Abstract: In the sexually dimorphic anteroventral periventricular nucleus (AVPV) of the hypothalamus, females have a greater number of tyrosine hydroxylase-immunoreactive (TH-ir) and kisspeptin-immunoreactive (kisspeptin-ir) neurons than males. In this study, we used proteomics analysis and gene-deficient mice to identify proteins that regulate the number of TH-ir and kisspeptin-ir neurons in the AVPV. Analysis of protein expressions in the rat AVPV on postnatal day 1 (PD1; the early phase of sex differentiation) using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
8
1
Order By: Relevance
“…Nagai et al (2015) recently showed that the number of apoptotic cells decreased in CRMP4-KO mice after spinal cord injury, compared with WT (Nagai et al 2015). In addition, we previously showed that a deficiency in CRMP4 affects the number of tyrosine hydroxylase-immunoreactive (TH) neurons in the sexually dimorphic nucleus of the mouse preoptic area in mice (Iwakura et al 2013). However, in the present study, few apoptotic cells were observed in the OB of either CRMP4-KO or WT neonates.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Nagai et al (2015) recently showed that the number of apoptotic cells decreased in CRMP4-KO mice after spinal cord injury, compared with WT (Nagai et al 2015). In addition, we previously showed that a deficiency in CRMP4 affects the number of tyrosine hydroxylase-immunoreactive (TH) neurons in the sexually dimorphic nucleus of the mouse preoptic area in mice (Iwakura et al 2013). However, in the present study, few apoptotic cells were observed in the OB of either CRMP4-KO or WT neonates.…”
Section: Discussioncontrasting
confidence: 75%
“…In addition, we previously showed that a deficiency in CRMP4 affects the number of tyrosine hydroxylase‐immunoreactive (TH) neurons in the sexually dimorphic nucleus of the mouse preoptic area in mice (Iwakura et al. ). However, in the present study, few apoptotic cells were observed in the OB of either CRMP4 ‐KO or WT neonates.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the focus was on CRMP4, which with CRMP2 synergistically regulates neuronal development (Niisato et al ., ) and is suggested to play an important role in the function of the cat visual cortex (Cnops et al ., ). Although a few studies using Crmp4 ‐knockout ( Crmp4 ‐KO) mice have been reported (Niisato et al ., ; Iwakura et al ., ; Khazaei et al ., ), no physiological or behavioral phenotypes of the mutant have been discovered. Because previously strong expression of Crmp4 mRNA in the olfactory bulb (OB) was found during the early postnatal period (Tsutiya & Ohtani‐Kaneko, ), suggesting crucial roles for CRMP4 in OB development, it was hypothesized that Crmp4 deletion would impair olfaction during this period.…”
Section: Introductionmentioning
confidence: 98%
“…CRMP4 is a member of the CRMP family of proteins (CRMP1–5) which are thought to regulate cell proliferation, migration, neuronal differentiation and signal transduction through their interaction with tubulin and actin 54 56 . Our previous proteomics study on the sexually dimorphic nucleus (AVPV) in the hypothalamic area, a region thought to be critical for generating the pre-ovulatory GnRH/LH surge in females, identified CRMP4 as a protein exhibiting sex-based differential expression during sexual differentiation of the nucleus 11 , although Crmp4 function in the sexual differentiation of AVPV remains unclear. Some studies have shown that CRMP4 negatively regulates axonal growth 57 60 , while others have shown its positive regulation of axonal elongation 61 , 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous proteomics studies identified collapsin response mediator protein 4 (CRMP4), also called DPYSL3, a member of the CRMP family (CRMP1–5), as a protein exhibiting sex-associated differences in expression during differentiation of the sexually dimorphic nucleus of the hypothalamus 11 . In addition, the expression of Crmp4 mRNA in the hypothalamic sexually dimorphic nucleus on post-natal day 0 (PD0) was altered in females treated with androgen during the late pre-natal stage 11 , indicating that Crmp4 expression is sex-steroid dependent in the rat, at least in this specific brain region.…”
Section: Introductionmentioning
confidence: 99%